Gambaran Prinsip Good Governance dalam Kebijakan Gerakan Masyarakat Hidup Sehat - Auryn, Shania; Agushybana, Farid; Widjanarko, Bagoes (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
The presence of comorbid diseases has become a crucial concern in confronting the COVID-19 pandemic, underscoring the need for the implementation of GERMAS (Healthy Living Movement) policy as a preventive measure initiated by the government. GERMAS aims to control the increase in non-communicable disease cases, which have the potential to disrupt human resources and productivity, as well as negatively impact social and economic development. In its implementation, GERMAS must adhere to the principles of Good Governance to ensure transparency, community participation, accountability, effectiveness, efficiency, responsiveness, and consensus. This research aims to analyze Transparency, Participation, Accountability, Effectiveness and Efficiency, Responsiveness, and Consensus. This research employs a qualitative approach with a narrative method and in-depth interviews with 12 informants. While GERMAS has been implemented since the President's directive in 2017, there are still several challenges in enhancing its effectiveness. Analysis of Good Governance principles highlights issues such as lack of community participation, low transparency and inter-agency coordination, and insufficient attention to inactive GERMAS forums. Further research is needed to deepen understanding of GERMAS implementation in Kutai Barat, focusing on aspects such as inter-sectoral communication, community participation, and enhancement of accountability of relevant agencies. Concrete steps such as comprehensive performance audits and increased social media outreach can help improve policy implementation.